Familial breast cancer: genetic counseling over time, including patients´ expectations and initiators considering the Angelina Jolie effect - Evers, Christina; Fischer, Christine; Dikow, Nicola; Schott, Sarah (PLOS ONE, 2017)
Purpose: The German Consortium for hereditary breast/ovarian cancer (GC-HBOC) aims for nationwide access to professional, individualized yet structured care for families at high risk. The identification of such families remains key for optimal care. Our study evaluates counselees’ characteristics, referral practices, expectations and motivations in respect to their first genetic consultation. The impact of the Angelina Jolie Effect (AJE) was prospectively assessed. Methods All counselees could participate through a questionnaire. Groups were built in respect to neoadjuvant chemotherapy (FT) and before/after AJE. Results The 917 (88.5%) counselees (FT: 8.2%) were on average female (97.3%), with a mean age of 44.6, had children (71.9%), higher education (88%), personal (46.4%) or at least one first-degree relative (74.6%) with BC/OC or known BRCA1/2 mutation (11.8%), were in a relationship (76.1%), and living in a village (40.7%). The AJE is associated with significantly fewer cancelations (p = 0.005), more attendance among men (4.2% vs. 0.8%, p = 0.002), and people with familial BRCA1/2 (14.8% vs. 7.5%, p = 0.003). The majority seek information regarding their cancer risk (83%) or relatives’ risk (74.8%), HBOC (69.1%), and surveillance programs for themselves (66.6%) or relatives (60.6%). Conclusion Enhanced media awareness of genetic cancer motivates patients, including other patient groups. A higher number of participants, including more men, are attending GC due to the AJE. In terms of the rising complexity of genetic testing, the analysis of patients’ expectations and initiators for GC suggests that there is an urgent need to develop to participate motivation analysis. The factors revealed as impediments to accessing GC-HBOC guide recommendations to optimize access to genetic counseling. Medical educational programs for primary gynecologists and families at risk might be options to reach more participants.